MULTIFUNCTIONAL VILLAGE HALL WITH SUSTAINABLE ARCHITECTURE CONCEPT: AN INTEGRATED LAND USE SYSTEM BY CONSIDERING BUILDING ENERGY EFFICIENCY - Laras Ayu; Ahmad Daris Maimun; Cynthia Permata Dewi (Journal Innovation of Civil Engineering (JICE), 2021)
Environmental pollution is one of the world's problems that is in the spotlight and can be related to all aspects, one of which is social inequality and also economic problems. To solve this problem, the United Nations together with UN member countries created sustainable development goals, which have 17 goals and 169 main targets and are expected to be fully realized by 2030. One of the sustainable development goals that is the focus of attention is goal number 9 on infrastructure. , industry, and innovation. Based on these reasons, this paper will discuss sustainable architecture with reviews of various existing studies as one of the efforts to support and fulfill aspects of the Sustainable Development Goals themselves. In the discussion of this paper, the author focuses on the innovation of multifunctional public infrastructure with land use and energy efficiency as a solution to existing social problems. With this research, it is proven that the use of sustainable architecture can be a solution in overcoming the problems of land use and energy efficiency